Influence of Vetiver Root System on Mechanical Performance of Expansive Soil: Experimental Studies - Guiyao Wang; Yonggang Huang; Runfa Li; Jingmei Chang; Jinliang Fu (Advances in Civil Engineering)
In order to study the influence of the vetiver root system on the swelling characteristics and crack resistance of expansive soil, vetiver grass root growth and its vertical distribution were investigated by the cultivation test and observation. The expansion rate experiment without load and expansive force tests was conducted on planted grass root soil samples, and the effect of the root content on the expansion rate and force of soil mass was analyzed. Finally, the effects of different vetiver contents on the crack resistance of expansive soil were studied by soil cracking experiments in an outdoor natural environment. The results showed that on account of the reinforcement effect of crisscrossing and winding grassroots, the expansion rate and expansive force can be reduced by the grass roots, and the grass roots can significantly increase the anticracking properties of the root-soil composites. From the surface down, the inhibition effect of the vetiver root on the expansive soil appeared from low to high and then decreased; the effect was optimal in the layer of 10∼15 cm. Compared with the pure expansive soil, the swelling force of the cultivated root expansive soil growing for 180 d decreased by more than 80%, and the unloaded expansive soil reduced by more than 70%. Compared with pure expansive soil, the swelling force and the unloaded expansion rate of cultivated root expansive soil growing for 90 d decreased by more than 50%.